What do their footprints tell us? Many questions and some answers about the life of non‑avian dinosaurs - Díaz Martínez, Ignacio (2024)
Fil: Díaz Martínez, Ignacio. Departamento de Ciencias de la Tierra y Física de la Materia Condensada, Facultad de Ciencias, Universidad de Cantabria, 39005 Santander, Cantabria, Spain